Assessing the Students’ Use of Cohesive Devices in Writing Hortatory Exposition Text - Hermin Wijayanti; Suwandi Suwandi; Sri Wuli Fitriati (English Education Journal, 2023)
This research began in the challenging of writing Hortatory Exposition Text, faced by students, especially second language learners in academic settings. Despite writing's crucial role in analysis and communication, limited structured practice leads to incoherent expression. Qualitative descriptive was applied to analyze the use of cohesive devices proposed by Halliday and Hasan’s (1976) theory. The object of this research were fifteen students of SMA Kesatrian 2 Semarang. The students’ texts were analyzed by using Halliday and Hasan’s (1976) theory. The findings show 336 grammatical and 138 lexical cohesions in the reading passages. The grammatical consisted of 170 (35.9%) references, 3 (0.6%) substitutions, 28 (5.9%) ellipses, and 135 (28.5%) conjunctions and the lexical cohesion consisted of 82 reiterations (17.3%) and 56 (11.8%) collocations. Hopefully, this research offers insights, particularly to English teachers, enhancing their ESL teaching approaches and addressing students' challenges more effectively.